Exploring Community Pharmacists' Knowledge, Attitudes, And Perceptions Towards Pharmacovigilance: A Cross-Sectional Study - Hamid Ahmed, Ahmed Abdalla; Ahmed Adem, Musab; Merghani, Abutalib; Algurshi, Tarig Mohmd; Abduelhadi Osman, Ahmed Awad; Veerendra, Uppara; Jollireddy, Sravani (Journal of Neonatal Surgery, 2025)
Background: Adverse Drug Reactions (ADRs) pose a significant public health concern, and effective pharmacovigilance is crucial for ensuring drug safety. Community pharmacists are vital in detecting and reporting ADRs as frontline healthcare professionals. However, their knowledge, attitudes, and practices (KAP) regarding pharmacovigilance in India need thorough evaluation, especially given the low ADR reporting rates despite the presence of the Pharmacovigilance Programme of India (PvPI). Objectives: This study aimed to assess the knowledge, explore the attitudes, and identify factors influencing the knowledge and attitudes of community pharmacists towards pharmacovigilance concepts, regulations, and reporting procedures in Anantapur, Andhra Pradesh, India. Methodology: A cross-sectional survey was conducted using a self-administered, validated questionnaire among 119 community pharmacists selected via convenient sampling. The questionnaire assessed knowledge (7 questions), attitudes (6 questions), and perceptions (7 questions) related to pharmacovigilance, along with demographic information. Data were analysed using descriptive statistics and chi-square tests with GraphPad Prism 7.0. Ethical approval was obtained. Results: The majority of participants were male (74.8%) and aged 21–35 years (63.0%), with diploma holders forming the largest educational group (54.6%). The mean knowledge (4.2/7) and attitude (3.8/6) scores indicated moderate competency, while perception scores were higher (5.1/7). Higher education levels significantly correlated with better knowledge (p=0.002*), and training positively influenced attitudes (p<0.01). An inverted U-curve relationship was observed between work experience and knowledge (p=0.03*). Qualification level and training were strong positive predictors of overall KAP scores in multivariate analysis. Conclusion: Community pharmacists in this South Indian region possess moderate knowledge and attitudes towards pharmacovigilance, with a more positive perception. Educational attainment and training are key determinants of their competency. Targeted educational interventions, simplified reporting mechanisms, and a supportive work environment are crucial to enhance their active participation in the national pharmacovigilance system and improve patient safety.